PENGARUH PRESTASI BELAJAR DAN MOTIVASI BERPRESTASI TERHADAP KESIAPAN BERWIRAUSAHA PADA SISWA SMK NEGERI 1 CERME GRESIK - Fauzia, Ellya (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2013)
The objective of this study is to investigate the effect of academic achievement on the entrepreneurship readiness, achievement motivation on the entrepreneurship readiness and both academic achievement and achievement motivation on the entrepreneurship readiness. The population covers 515 students coming from 6 different classes. The samples are 87 students taken from 2 classes of Grade XII Multimedia department and 1 class of Industrial Chemistry. Data were collected using questionnaire. Regression analysis of F-test and t-test were employed to analyze the data. The finding indicates that operational t coefficient of the academic achievement is 4.093 (d.f.: 0.000) and the achievement motivation is 2.350 (d.f.: 0.000). In addition, the operational F coefficient of both academic achievement and achievement motivation is 12.456 (d.f.: 0.000). In conclusion, academic achievement positively influences students entrepreneurship readiness and so does achievement motivation. Accordingly, both variables influence the students entrepreneurship readiness.